Causes of global extinctions in the history of life: facts and hypotheses - T. M. Khlebodarova; V. A. Likhoshvai (Вавиловский журнал генетики и селекции)
Paleontologists define global extinctions on Earth as a loss of about three-quarters of plant and animal species over a relatively short period of time. At least five global extinctions are documented in the Phanerozoic fossil record (~500-million-year period): ~65, 200, 260, 380, and 440 million years ago. In addition, there is evidence of global extinctions in earlier periods of life on Earth – during the Late Cambrian (~500 million years ago) and Ediacaran periods (more than 540 million years ago). There is still no common opinion on the causes of their occurrence. The current study is a systematized review of the data on recorded extinctions of complex life forms on Earth from the moment of their occurrence during the Ediacaran period to the modern period. The review discusses possible causes for mass extinctions in the light of the influence of abiogenic factors, planetary or astronomical, and the consequences of their actions. We evaluate the pros and cons of the hypothesis on the presence of periodicity in the extinction of Phanerozoic marine biota. Strong evidence that allows us to hypothesize that additional mechanisms associated with various internal biotic factors are responsible for the emergence of extinctions in the evolution of complex life forms is discussed. Developing the idea of the internal causes of periodicity and discontinuity in evolution, we propose our own original hypothesis, according to which the bistability phenomenon underlies the complex dynamics of the biota development, which is manifested in the form of global extinctions. The bistability phenomenon arises only in ecosystems with predominant sexual reproduction. Our hypothesis suggests that even in the absence of global abiotic catastrophes, extinctions of biota would occur anyway. However, our hypothesis does not exclude the possibility that in different periods of the Earth’s history the biota was subjected to powerful external influences that had a significant impact on its further development, which is reflected in the Earth’s fossil record.